Gruau : portraits of men - Bargiel, Réjane; Nissen, Sylvie (New York : Assouline Pubishing, 2012)
Primarily known for his colorful and vivacious portrayals of women, Rene Gruau revolutionized the concept of masculinity in fashion imagery and advertising from the 1950s to the '80s, depicting the modern casual, confident man with humor and sex appeal--including images of partial male nudity that were considered shocking at the time.
boek
Keywords: Gruau, René